Depuration of gut contents in the intertidal snail Nerita lineata is not necessary for the study of heavy metal contamination and bioavailability: a laboratory study - Yap, Chee Kong; Cheng, Wan Hee (Universiti Putra Malaysia Press, 2010)
Some of the scientific papers in the literature regarding heavy metal concentrations in the soft tissues of molluscs are always rejected because there is no depuration of metals before the molluscs samples are analyzed for heavy metal accumulation, although the acceptance of a paper in a journal is assessed based on many other factors. The depuration of gut contents of molluscs has been the initial step before the metal analysis on the soft tissues of molluscs by many researchers. The depuration process in some molluscs involves holding the animals in clean water or clean sediment for a suitable period (8–24 hrs) to purge their guts after exposing them to contaminated conditions, and before they are analyzed for whole-body contaminant burden (Neumann et al., 1999; Gillis et al. , 2004). The depuration ensures that metal-contaminated particles in the animal’s gut do not lead to overestimation of metal bioavailability. Undoubtedly, clearing the gut contents is theoretically a laboratory technique in order to get an accurate estimate of heavy metal concentrations accumulated in the soft tissues of molluscs. In addition, the suggestion on the use of molluscs as biomonitors of metal bioavailability becomes invalid because their soft tissues were not depurated. Consequently, validity on the data of metal concentrations could not be achieved. Therefore, in order to determine if a particular species could be used as biomonitor for metals, depuration of soft tissues of the molluscs is imperative to effectively determine the availability of metal (Riba et al. , 2005; Wang et al. , 2005; Szefer et al. , 1999; Cravo et al. , 2004; Baldwin and Maher, 1997; Nicholson and Szefer, 2003). In standard protocols (ASTM, 2003), although it is not a standard practice to clear the gut of organisms before analyzing their tissues for whole-body metal accumulation, some investigators do transfer animals to clean water conditions in order to purge their guts after they have been collected from the field. In this study, the snail known as Nerita lineata of the Neritidae family, were collected to study if there was any significant difference in the concentrations of Cu and Zn in the soft tissues, before and after four weeks of depuration.